Economic Partnership Agreements: implications for regional governance and EU-ACP development cooperation - Merran Hulse (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The controversial Economic Partnership Agreements (EPAs) are currently back on the agenda, as several African, Caribbean and Pacific (ACP) states are again faced with a loss of market access if they do not ratify their EPAs by 1 October 2016. To complicate matters, Brexit has introduced an element of uncertainty and is causing some ACP states to reconsider their decision to sign EPAs. EPAs were introduced under the trade pillar of the Cotonou Partnership Agreement (CPA), which governs relations between the European Union (EU) and the ACP. EPAs represent a sea change in trade relations between the EU and the ACP: not only do they introduce reciprocity into trade preferences, they are organized on a regional basis, with the aim of promoting regional integration within the ACP. This Briefing Paper presents an update of the various EPA processes, and investigates the extent to which they have actually met the EU's stated aim of promoting regionalism in the ACP, as well as the EPAs alignment with the Sustainable Development Goals (SDGs), and the debate on the future of EU-ACP cooperation. EPAs have been only partially effective in facilitating regional integration in the ACP. EPA negotiations have resulted in the conclusion of region-wide deals that align with existing integration initiatives in only three regions: the Caribbean, the East African Community (EAC), and West Africa. EPAs have acted as a `mid-wife' to deeper integration in these regions, however it is a possibility that the EAC and West African EPAs will not be signed by the October deadline. In the remaining regions – the Pacific, Central Africa, Eastern and Southern Africa (ESA), and the Southern African Development Community (SADC) – EPAs have made future prospects for regional integration more difficult, and in some cases may have contributed to a `lock-in' of fragmented regionalism. Part of the reason for this mixed record is tension between the CPA's principles of `regionalization', which recognizes the importance of regional integration for development; and `differentiation', which advocates treating states differently based on their level of development. EPAs aimed to encourage groups of states to sign the agreements as regional blocs, but the EU's Everything But Arms (EBA) regime undermines regional EPAs by offering Least Developed Countries (LDCs) non-reciprocal trade preferences. This splits ACP regions into LDCs versus non-LDCs, making it difficult to conclude regional EPAs. Given the ongoing struggle to conclude regional EPAs, and the uncertainty of Brexit, the EU should consider extending the 1 October deadline, to allow ACP states more time to consider their positions and work on further harmonising regional relations. As regional integration is key for the economic development of ACP states, future cooperation should be aware of the need for alignment of EPAs, the SDGs, and the goal of regional integration.
Keywords: 330; Handel und Investitionen; Regionale + globale + transnationale Governance